FAKTOR-FAKTOR YANG MEMPENGARUHI TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DASAR DAN KIMIA - Tika, Tika Purbawati; Endang Masitoh; Dimas Ilham Nur Rois (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
The reason of this research is to analyze the influence of profitability, institutional ownership, company size, capital intensity ratio and financial distress on tax avoidance in basic industrial and chemical companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The research population was 91 companies. Determining the sample in the research used a purposive sampling method and obtained 32 companies with certain criteria. The total number of research data for 4 years was 128. Multiple linear regression analysis is the method employed in this study. The findings of the study indicate that while institutional ownership, company size, and financial distress hadn’t bearing on tax avoidance, profitability and capital intensity ratio do.